Last twilight in Paris [large type] - Jenoff, Pam (Thorndike Press large print dynamic drama., 2025)
"London, 1953. Louise is still adjusting to her postwar role as a housewife when she discovers a necklace in a box at a secondhand shop. The box is marked with the name of a department store in Paris, and she is certain she has seen the necklace before, when she worked with the Red Cross in Nazi-occupied Europe--and that it holds the key to the mysterious death of her friend Franny during the war. Following the trail of clues to Paris, Louise seeks help from her former boss Ian, with whom she shares a romantic history. The necklace leads them to discover the dark history of Lévitan--a once-glamorous department store that served as a Nazi prison, and Helaine, a woman who was imprisoned there, torn apart from her husband when the Germans invaded France. Louise races to find the connection between the necklace, the department store and Franny's death. But nothing is as it seems, and there are forces determined to keep the truth buried forever. Inspired by the true story of Lévitan, Last Twilight in Paris is both a gripping mystery and an unforgettable story about sacrifice, resistance and the power of love to transcend in even the darkest hours"--